The Untold Struggles of Lecturers in Ghana’s Colleges of Education: Stresses, Burn Out and Emotional Illness - Entsie, Nasir Yaqub; Owusu-Cole, Clement; Agyemang, Simon Mawulorm; Danyoh, James Divine; Akore, Ernest Sarpong; Asante, Joseph Serebour; Darkoa, Margaret (International Journal of African Higher Education, 2025)
This study examined the impact of stress and burnout on the well-being of lecturers within Ghana's evolving Colleges of Education (CoEs). The transformation of CoEs from traditional teacher training institutions to degree-awarding entities has shifted demands and expectations, posing challenges to lecturers' physical and mental health. Addressing a critical gap in research, this study focused on this specific context. The research design employed a cross-sectional descriptive approach to capture the dynamic relationships over time. Using the multistage sampling technique, a structured questionnaire was used to collect data from 610 lecturers encompassing various disciplines and experience levels across 13 CoEs, The quantitative analysis revealed significant positive correlations between stress, burnout, and lecturers' physical health (r = .368, p = .012; r = .382, p = .009). The shift in CoE demands, including increased workload and technology integration, contribute to back pain, tiredness, and breathing difficulties. Burnout's emotional exhaustion and reduced accomplishment also impact lecturers' mental health, resulting in anxiety, depression, and concentration difficulties (r = .373, p = .001; r = .376, p = .013). These findings underscore the interconnectedness of stress, burnout, physical health, and mental health. The study highlights the need for holistic interventions, including stress management and mental health support, to enhance educators' well-being and maintain the quality of educational services within CoEs. The research contributes by addressing the dearth of context-specific data and extending theoretical frameworks. It emphasises the urgency of fostering a supportive environment amidst CoE transformation. This study informs educational institutions' efforts to prioritise lecturers' well-being in the changing educational landscape.